1999
DOI: 10.1039/a905277a
|View full text |Cite
|
Sign up to set email alerts
|

Anion recognition and luminescent sensing by new ruthenium(II) and rhenium(I) bipyridyl calix[4]diquinone receptors

Abstract: New ruthenium(ii) and rhenium(i) bipyridyl calix[4]diquinone receptors have been prepared and shown to selectively bind and sense acetate anions via remarkable luminescent emission intensity retrieval effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(50 citation statements)
references
References 10 publications
1
48
0
1
Order By: Relevance
“…While there are no previous examples of Re(CO)3X moieties being appended to CTV-type host molecules, there are a number of reports of other classes of macrocyclic host molecules being decorated in this fashion. For example, decoration of calixarenes with [Re(CO)3X(bpy) (Bpy = 2,2'-bipyridyl) groups at the upper 18,19 or lower calixarene rim 20,21 have been reported, and includes cases of complexes showing luminescence sensing behavior for fullerenes 18 or anions. 20 The Re(CO)3Br unit has also been employed as a building tecton to link pyridyl appended cavitands into ditopic cavitand assemblies, 22 and as metallobridges to stabilize the extended cavity of an expanded calix [4]arene.…”
Section: Tris-(bromo-fac-tricarbonylrhenium(i)) Complexes Of Ctg-typementioning
confidence: 99%
See 1 more Smart Citation
“…While there are no previous examples of Re(CO)3X moieties being appended to CTV-type host molecules, there are a number of reports of other classes of macrocyclic host molecules being decorated in this fashion. For example, decoration of calixarenes with [Re(CO)3X(bpy) (Bpy = 2,2'-bipyridyl) groups at the upper 18,19 or lower calixarene rim 20,21 have been reported, and includes cases of complexes showing luminescence sensing behavior for fullerenes 18 or anions. 20 The Re(CO)3Br unit has also been employed as a building tecton to link pyridyl appended cavitands into ditopic cavitand assemblies, 22 and as metallobridges to stabilize the extended cavity of an expanded calix [4]arene.…”
Section: Tris-(bromo-fac-tricarbonylrhenium(i)) Complexes Of Ctg-typementioning
confidence: 99%
“…For example, decoration of calixarenes with [Re(CO)3X(bpy) (Bpy = 2,2'-bipyridyl) groups at the upper 18,19 or lower calixarene rim 20,21 have been reported, and includes cases of complexes showing luminescence sensing behavior for fullerenes 18 or anions. 20 The Re(CO)3Br unit has also been employed as a building tecton to link pyridyl appended cavitands into ditopic cavitand assemblies, 22 and as metallobridges to stabilize the extended cavity of an expanded calix [4]arene. 23 In related work, the fac-Re(CO)3 unit has been used to build a variety of metallacyclic, metallacage or metallacavitand complexes.…”
Section: Tris-(bromo-fac-tricarbonylrhenium(i)) Complexes Of Ctg-typementioning
confidence: 99%
“…Similarly, the calix [4]arene appended complex 6d (Fig. 6) demonstrates a selectivity for OAc À with a marked revival of the quenched emissive behaviour on the introduction of the anions [63]. In another example, the inclusion of the positively charged pseudorotaxane thread within a macrocyclic complex (6e-6h; Fig.…”
Section: Rhenium(i) Carbonyl Complexesmentioning
confidence: 99%
“…[22][23][24][25][26] Several groups have employed luminiscent ruthenium complexes with substituted bipyridines as chemical sensors for anions. [27][28][29][30][31][32][33][34][35] More recently, Gale and Loeb have reported a series of platinum complexes with substituted pyridine ligands as metalla-receptors for anions 20,36,37 while Anslyn has demonstrated that copper complexes of tridentate ligands (with a C 3v symmetry) can selectively bind phosphates with high associations constants. 38 As part of our ongoing interest in developing metalla-receptors for anions, [39][40][41][42][43][44][45] we have recently reported in a preliminary communication the synthesis and crystal structure of di-palladium complex 1 (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%